How Do the Four Core Factors of High Entropy Affect the Electrochemical Properties of Energy‐Storage Materials? - Wenze Wang; Qian Zhang; Liting Yang; Guisheng Liang; Xuhui Xiong; Yifeng Cheng; Limin Wu; Chunfu Lin; Renchao Che (Advanced Science)
Abstract High‐entropy materials (HEMs) are extremely popular for electrochemical energy storage nowadays. However, the detailed effects of four core factors of high entropy on the electrochemical properties of HEMs are still unclear. Here, a high‐entropy La1/4Ce1/4Pr1/4Nd1/4Nb3O9 (HE‐LaNb3O9) oxide is prepared through multiple rare‐metal‐ion substitution in LaNb3O9, and uses HE‐LaNb3O9 as a model material to systematically study the effects of the four core factors of high entropy on electrochemical energy‐storage materials. The high‐entropy effect lowers the calcination temperature for obtaining pure HE‐LaNb3O9. The lattice distortion in HE‐LaNb3O9 leads to its decreased unit‐cell‐volume variations, which benefits its cyclability. Based on the restrained diffusion arising from the lattice distortion, the Li+ diffusivity of HE‐LaNb3O9 at room temperature (25 °C) is limited, which causes its lowered rate capability. However, the Li+ diffusivity of HE‐LaNb3O9 at high temperature (60 °C) becomes faster than that of LaNb3O9, which is attributed to the alleviated lattice distortion at the high‐temperature, resulting in higher rate capability. The cocktail effects in HE‐LaNb3O9 enable its larger electronic conductivity, better electrochemical activity, more intensive Nb5+ ↔ Nb3+ redox reaction, and larger reversible capacity. The insight gained here can provide a guide for the rational design of new HEMs with good energy‐storage properties.